MANAGEMENT THEORY AND TOTAL QUALITY: IMPROVING RESEARCH AND PRACTICE THROUGH THEORY DEVELOPMENT - Dean, James W.; Bowen, David E. (Academy of Management Review, 1994)
James W. Dean, Jr., David E. Bowen, Management Theory and Total Quality: Improving Research and Practice through Theory Development, The Academy of Management Review, Vol. 19, No. 3, Special Issue: "Total Quality" (Jul., 1994), pp. 392-418